Temperature drop and gelatinization characteristics of waxy crude oil in 1000 m3 single and double-plate floating roof oil tanks during storage - Wang, Min; Zhang, Xinyu; Shao, Qianqian; Li, Jingfa; Yu, Bo (International journal of heat and mass transfer, 2019)
•Temperature drop and gelatinization characteristics in floating roof oil tanks are studied.•Evolutions of the flow and heat transfer in these two tanks are investigated in detail.•Similarities and differences between these two tanks are compared and investigated. Single and double-plate floating roof oil tanks are two types of widely used floating roof oil tanks in petrochemical industry. However, the differences in flow and hear transfer characteristics of waxy crude oil inside these two tanks have been studied insufficiently. Finite volume method is employed in this research to study the temperature drop and gelatinization processes of waxy crude oil as well as the differences in single and double-plate floating roof tanks. Based on a comprehensive consideration of the atmosphere, soil, floating roof oil tank as well as the tank structure and the variations of the waxy crude oil state and rheological behavior, general physical and mathematical models are established. In the model, wax precipitation and gelatinization processes of waxy crude oil are described by the enthalpy-porous media method. Non-Newtonian behavior is described by the Power law equation. Turbulent natural convection is described by the LES method. SIMPLE algorithm is employed to couple pressure and velocity. Taking 1000 m3 single and double-plate floating roof oil tanks as examples, the evolution of oil temperature and flow behavior is studied and the variations of the gel oil thickness and heat flux are analyzed. Moreover, the differences between these two tanks are also discussed. Results show that due to the structure difference of the tank roof, the temperature drop rates are 0.018 °C/h and 0.007 °C/h respectively in single and double-plate floating roof tanks in the case of this research. Secondly, for the growth of gel oil on tank bottom, in double-plate floating roof tank, gel oil thickness keeps growing and fluctuating, while in single-plate tank, the original gelled oil layer disappears firstly and then increases gradually. Thirdly, although for both tanks, tank roof is the main part of heat dissipation towards the atmosphere, the maximum heat fluxes are respectively over 2.0 kW and 0.4 kW for single and double-plate floating roof tanks, and the total average heat fluxes respectively are 1.49 kW and 0.59 kW.